THE DEVELOPMENT OF STUDENT WORKSHEETS PREDICT-OBSERVE-EXPLAIN- BASED ON NATURAL SCIENCE LESSONS OF THE FOURTH GRADE - Dameis Surya Anggara; Candra Abdillah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This study aims to produce teaching materials in the form of Predict-Observe-Explain-based student worksheets in the fourth grade on natural science lessons with the theme of Always Saving Energy which are valid, practical, and effective in improving understanding of the concepts. The research approach used mixed methods with the Research and Development (R&D) methodology with procedures consisting of 4 steps namely 1) define, 2) design, 3) develope, 4) disseminate. Furthermore, the data collection instruments used questionnaire for product validation by experts, teacher response questionnaire, and items about understanding the concept of science. Data collected sequentially were analyzed using the Content Validity Index (CVI), Descriptive Statistics, and Independent Sample t Test. The results obtained were Predict-Observe-Explain student worksheets: 1) content valid criteria with a CVI value of 0.9, 2) good practicality criteria with a percentage of 79.56%, and 3) effective criteria in increasing understanding of the concept of Natural Sciences with evidence of a significant difference between an increase in the average understanding of the concept of experimental class science by 21.3750 higher than the increase in understanding of the concept of science in the control class of only 16.2500.